Perlindungan Hukum Terhadap Investor Dalam Kegiatan Investasi Digital Di Indonesia - bari, Abdulbari; Raodah, Putri (Departement Business Law, Faculty of Law, University of Mataram, 2024)
The purpose of this research is to determine the legal protection for investors in digital investment activities in Indonesia, namely Law No. 8 of 1999 concerning Consumer Protection, Law No. 25 of 2007 concerning Capital Investment, Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE), and BAPPETI Regulation No. 7 of 2022 concerning Determining the List of Crypto Assets That Can Be Traded. This research uses a type of empirical normative research. The study results and discussion of digital investment, such as cryptocurrency, create a legal relationship between investors and traders with rights and obligations regulated by CoFTRA regulations and the Currency Law. Investors have the right to clear information, benefits, and are obliged to understand risks and regulations. Traders are entitled to compensation and must provide information and protect investors' assets. The Investment Law and other rules protect investors, including the Consumer Protection Law and the Information and Electronic Transaction Law. This protection is essential to ensure investor safety from online investment risks, including illegal investments. The strategies to provide legal protection for investors are education, strengthening regulations and supervision, and implementing the precautionary principle. Law enforcement is also essential, including dispute resolution, criminal prosecution, and compensation. Firm and effective law enforcement can help prevent and eradicate illegal investment practices, protect, build trust and security, and encourage digital economic growth in Indonesia.